Understanding the dimensions of patriotism: a literature highlight - Ku Samsu, Ku Hasnita (Human Resource Management Academic Research Society, 2022)
Patriotism refers to a good value that benefits the country as a whole. Every citizen must be patriotic to ensure the survival of the country. They need to understand and appreciate the dimension of patriotism first to ensure patriotism is well understood as best as possible. However, some scholars discuss the pros and cons of patriotism that affect the understanding of patriotism meaning. Therefore, this paper aims to discuss in detail the dimensions of patriotism to avoid confusion regarding the actual meaning of patriotism. Hence, secondary data analysis from previous literature consisting of books, book chapters, and journal articles has been done to discuss the dimension. The results of the discussion highlighted six dimensions of patriotism: ego-centric patriotism, value-based patriotism, uncritical/authoritarian patriotism, constructive patriotism, fair patriotism and nationalism in the context of patriotism. The discussion can help readers classify true patriotism and vice versa.